Return on investment from service transformation for young people experiencing mental health problems: Approach to economic evaluations in ACCESS Open Minds (Esprits ouverts), a multi-site pan-Canadian youth mental health project - Shah, Jai L.; Moinfar, Zeinab; Anderson, Kelly K.; Gould, Hayley; Hutt-Macleod, Daphne; Jacobs, Philip; Mitchell, Stephen; Nguyen, Thanh; Rodrigues, Rebecca; Reaume-Zimmer, Paula; Rudderham, Heather; Rudderham, Sharon; et al. (Frontiers in Psychiatry, 2023)
Introduction: Mental health problems are common globally, and typically have their onset in adolescence and early adulthood – making youth (aged 11-25) an optimal target for prevention and early intervention efforts. While increasing numbers of youth mental health (YMH) initiatives are now underway, thus far few have been subject to economic evaluations. Here we describe an approach to determining the return on investment of YMH service transformation via the pan-Canadian ACCESS Open Minds (AOM) project, for which a key focus is on improving access to mental health care and reducing unmet need in community settings. Approach: As a complex intervention package, it is hoped that the AOM transformation will: (i) enable early intervention through accessible, community-based services; (ii) shift care away towards these primary/community settings and away from acute hospital and emergency services; and (iii) offset at least some of the increased costs of primary care/community-based mental health services with reductions in the volume of more resource-intensive acute, emergency, hospital or specialist services utilized. Co-designed with three diverse sites that represent different Canadian contexts, a return on investment analysis will (separately at each site) compare the costs generated by the intervention, including volumes and expenditures associated with the AOM service transformation and any contemporaneous changes in acute, emergency, hospital or service utilization (versus historical or parallel comparators). Available data from health system partners are being mobilized to assess these hypotheses. Anticipated Results: Across urban, semi-urban and Indigenous sites, the additional costs of the AOM transformation and its implementation in community settings are expected to be at least partially offset by a reduction in the need for acute, emergency, hospital or specialist care. Discussion: Complex interventions such as AOM aim to shift care ‘upstream’: away from acute, emergency, hospital and specialist services and towards community-based programming which is more easily accessible, often more appropriate for early-stage presentations, and more resource-efficient. Carrying out economic evaluations of such interventions is challenging given the constraints of available data and health system organization. Nonetheless, such analyses can advance knowledge, strengthen stakeholder engagement, and further implementation of this public health priority.